Improving Islamic Religious Education Learning Outcomes Using the Problem Based Learning Model: A Study at SMA Negeri 1 Situjuah Limo Nagari - Putra, Hendra (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the Problem based learning model for students. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Problem based learning model can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.11%, the first cycle 72.69% and in the second cycle increased to 93.16%. Thus, the use of the Problem based learning model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.